Antimicrobial resistance in Streptococcus pneumoniae: mechanisms and current epidemiology - da Cunha, Gabriela Rosa; Caierão, Juliana; d’Azevedo, Pedro Alves; Dias, Cícero Armídio Gomes (Clinical and Biomedical Research, 2014)
Infections caused by Streptococcus pneumoniae are a worrisome public health problem worldwide. Young children and the elderly are the main age groups affected and the highest burden of the disease is found in developing countries. Pneumococcal infections cause 11% of the total infant deaths, representing the leading cause of child death currently preventable by vaccination. Epidemiologic information about pneumococci in Brazil is somehow restricted, but available data reinforce the worrisome occurrence of pneumococcal diseases, which are commonly treated empirically. Limitations in the diagnostic methods, along with the severity of disease contribute to this behavior. Thus, surveillance studies are crucial to define the prevalence of resistant strains both globally and in a particular region, as these strains may compromise empirical therapeutic choices. However, although different clones of penicillin non-susceptible pneumococci are internationally distributed, and considering diseases other than meningitis, the prevalence of resistance to penicillin is quite low, making this old, safe, and inexpensive drug an attractive first choice to treat pneumococcal infections. The widespread use of conjugate vaccines among children, influencing the circulation of resistant clones and the distribution of serotypes reinforces the need of surveillance studies to define the prevalence of resistance.